The low-pressure partial-melting behaviour of natural boron-bearing metapelites from the Mt Stafford area, Central Australia - Spicer, Esme Marelien (Stellenbosch : University of Stellenbosch, 2011)
Thesis (DSc)--University of Stellenbosch, 2011.